ANALISIS PERANCANGAN USAHA PEMBUATAN PENIRIS MINYAK (SPINNER) SEDERHANA UNTUK UMKM - Saputra, Dhimas Indra; Muzakki, Ahmad Syahri; Prasetya, Alfadito Noval; Rohman, Fatchur; Kurniawan, Moh Dian (JUSTI (Jurnal Sistem dan Teknik Industri), 2023)
Indonesian people, especially the lower middle class, often survive by establishing MSMEs or Micro, Small and Medium Enterprises because in building MSMEs (Micro, Small and Medium Enterprises) does not require large capital and can be done in the owner's home, our research aims to ease the burden of capital or business from chip-making business owners on a small or micro scale so that business owners do not spend too much money when buying equipment, Our research focuses on the quality and durability of the products to be sold and the result of our research is to make an oil draining machine (spinner) with small dimensions and at a low price but with quality that is not cheap, after going through various cost analyses, we get a price for the sale of our machine which is Rp. 260,000.00 / unit., with an affordable price, a machine that has been made from foodgrade and powerful to drain the oil in the chips that have been fried